UPPER DEVONIAN CONODONTS FROM LADAKH, HIMALAYA, INDIA (Rivista italiana di Paleontologia e Stratigrafia, 2020)
The preserit paper describes Upper Devonian conodont fauna from the black and bluish limestone succession lying immediately above the Muth Quartzite exposed near the village Tanze, Luneak valley, Ladakh.